KANDUNGAN HARA MAKRO TANAH GAMBUT PADA PEMBERIAN KOMPOS Azolla pinata DENGAN DOSIS BERBEDA DAN PENGARUHNYA TERHADAP PERTUMBUHAN TANAMAN KANGKUNG (Ipomea reptans Poir) - ERVINA ARYANTI; HADISA NOVLINA; ROBBANA SARAGIH (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
Peat soil generally have pH leves, has a hight cation exchange capaticy, low base saturation, low K, Ca, Mg and P contain and it’s also has low micro element content. This study aims to determine the effect of composed Azolla pinata with different doses for Macro Fertility of Peat Soil and It’s Aplication in Plant Growth Kale. This research has been conducted in March to May 2015 in Experimental Farm of the Faculty of Agriculture and Livetock and Agrostology, Feed Industry and Siol Science Laboratory, State Islamic University Sultan Syarif Kasim Riau. This Research used non factorial Completly Randomized Design (CRD) of 6 levels: Without Azolla compost, 3 tons/ha (30 g), 6 tons/ha (60 g), 9 tons/ha (90 g), 12 tons/ha (120 g), 15 tons/ha (150 g). Each treatment was done 6 replications. The results showed that Azolla compost increasing macro fertility properties P on peat soil but not for pH, N and K. Based on analysis of variance 9 tons/ha dose is the best to increasing plant height, leaf number and fresh weight of plant.